PENCIPTAAN BUKU ILUSTRASI PERTEMPURAN 10 NOPEMBER 1945 SEBAGAI UPAYA MENINGKATKAN PENGETAHUAN DAN APRESIASI REMAJA TERHADAP SEJARAH KEMERDEKAAN - Perdana, Aditya Arif; riyanto, darwin yuwono; Hidayat, Wahyu (Jurnal Art Nouveau, 2016)
Abstract: Seeing the development of the modern era like this many young people who forget the history of Indonesiaâs Independence, a student does not understand when asked to identify the content of Sumpah Pemuda. The problem is, history among teenagers is not interesting thing to know and they lack an appreciation of the history of the nationâs independence. This is because the history books are not packaged attractively to encourage interest in teen learn about the history of independence as illustrated book about the story of the history of the independence of the Battle of 10 November 1945. Battle of 10 November 1945 is a heroic image of Indonesia in Surabaya, this event is a precursor for the resistances to the invaders that occurred in all regions of Indonesia. In this study showed that abdolescents have little knowledge of the history of independence and heroism Indonesia. For the purpose of this study was to create an illustrated book Battle of 10 November 1945 as an effort to promote the appreciation and knowledge of adolescents to the history of independence.